Reprogramming somatic cells to cells with neuronal characteristics by defined medium both in vitro and in vivo. Issue 1 (December 2015) - He, Songwei; Guo, Yiping; Zhang, Yixin; Li, Yuan; Feng, Chengqian; Li, Xiang; Lin, Lilong; Guo, Lin; Wang, Haitao; Liu, Chunhua; Zheng, Yi; Luo, Chuanming; et al.
Abstract Background Currently, direct conversion from somatic cells to neurons requires virus-mediated delivery of at least one transcriptional factor or a combination of several small-molecule compounds. Delivery of transcriptional factors may affect genome stability, while small-molecule compounds may require more evaluations when appliedin vivo . Thus, a defined medium with only conventional growth factors or additives for cell culture is desirable for inducing neuronal trans-differentiation. Results Here, we report that a defined medium (5C) consisting of basic fibroblast growth factor (bFGF), N2 supplement, leukemia inhibitory factor, vitamin C (Vc), and β-mercaptoethanol (βMe) induces the direct conversion of somatic cells to cells with neuronal characteristics. Application of 5C medium converted mouse embryonic fibroblasts (MEFs) into TuJ+ neuronal-like cells, which were capable of survival after being transplanted into the mouse brain. The same 5C medium could convert primary rat astrocytes into neuronal-like cells with mature electrophysiology characteristicsin vitro and facilitated the recovery of brain injury, possibly by inducing similar conversions, when infused into the mouse brainin vivo . Crucially, 5C medium could also induce neuronal characteristics in several human cell types. Conclusions In summary, this 5C medium not only provides a means to derive cells with neuronal characteristics without viral transfectionin vitro but might also be useful to produce neuronsin vivo for neurodegenerative disease treatment.